PELESTARIAN MANUSKRIP LONTAR: STUDI KASUS KAWASAN CAGAR BUDAYA NASIONAL TROWULAN - Fatihah, Lauhil; Riyanto, Edi Dwi (Metahumaniora, 2025)
Palm manuscripts are one of the rich cultural treasures of the Indonesian Nation that needs to be preserved, because they contain important values as a cultural heritage from the past and the preservation of palm manuscripts has currently been carried out, both by the community and the government. The Trowulan National Cultural Heritage Area is a conservation area protected by the Indonesian Government which also has cultural heritage in the form of palm manuscripts. Currently, the lontar manuscripts preserved in the area are managed by the Majapahit Information Management Unit, which is one of the units of Balai Pelestarian Kebudayaan Wilayah XI. This research aims to find out how the process of preserving lontar manuscripts, both as Cultural Heritage and Cultural Promotion Objects in the Trowulan National Cultural Heritage Area. This research is a quantitative research that uses a case study of lontar manuscripts in the Trowulan National Cultural Heritage Area. The data sources used in this research are primary data in the form of direct observation of palm manuscript collections and in-depth interviews with related parties, while secondary data are archival documents, policy reports, scientific publications, and other references related to palm manuscript preservation. This research uses data collection methods in the form of participatory observation, in-depth interviews, and document studies. The data analysis methods used in this research are data reduction, thematic categorization, contextual interpretation, verification and triangulation. The results of this study are that the preservation of palm manuscripts in the Trowulan National Cultural Heritage Area is carried out through efforts to preserve palm manuscripts as Cultural Heritage and as Objects of Cultural Advancement, but there are obstacles and challenges in the preservation process, namely in the form of natural factors and limited human resources.